Emergency management plan for paediatric patients with tracheostomies during the coronavirus disease 2019 pandemic. Issue 12 (5th December 2022) - Petulla, B; Ho, E; Sov, E; Soma, M
Abstract: Objectives: Paediatric patients with tracheostomies are a vulnerable group. During the coronavirus disease 2019 pandemic, healthcare workers can be anxious about viral transmission from secretions and aerosols emerging from the open airway. This paper aims to share a systematic approach to decrease staff exposure and optimise care of these patients. Methods: Three documents were developed: a generic tracheostomy management plan detailing troubleshooting; a personalised management plan with customised recommendations; and a guide for tracheostomy tube change to minimise aerosol production. Results: The plan was distributed to 31 patients (age range, 11 months to 17 years) including 23 (74.2 per cent) with uncuffed tubes and 9 (29 per cent) on long-term ventilation. There have been 10 occasions in which the plan was utilised and influenced management. Conclusion: A structured approach to emergency presentations during the coronavirus disease 2019 pandemic may safeguard paediatric patients from unnecessary manipulation of their tracheostomy tube, minimise viral exposure and allow provision of expeditious care.